Comparison of covid-19 case fatality rates in high altitude areas in Peru - Canchucaja-Bendezú, Milagros (2023)
Introduction. COVID-19 infection in high-altitude districts has been a subject of study for several researchers since the incidence and transmission capacity of this virus is lower at higher altitudes. Objective. Compare the lethality of COVID-19 at different altitudes in different districts of Peru. Material and Methods. We conducted a secondary descriptive observational study based on data from the Ministry of Health, we took as a unit of analysis 1874 districts of Peru, taking the fatality rate as the dependent variable. In our main analysis, we developed a crude and cofactor-adjusted linear regression between the COVID-19 case fatality rate per million inhabitants and altitude of residence of the districts of Peru, we also carried out two sensitivity analyzes, to provide different approaches to the problem, adding two multivariate regression models as a sensitivity analysis, all the analyzes were crudely and adjusted estimated, with their respective 95% confidence intervals (95%CI). Results. The average case fatality rate of each district located at less than 1500 m.a.s.l. was 415.49% per hundred million inhabitants, while at more than 3500 m.a.s.l., it decreased by almost half. However, when performing the analysis adjusted for confounders, population density and poverty quintile, it was observed that there was no statistically significant difference (p=0.359). Conclusions. Our findings show that although at higher altitudes above sea level, there is a lower-case fatality rate, this value is not clearly attributed to altitude.